A Wideband Circularly Polarized Antenna Array Using Irregularly Shaped Hexagonal Slot Optimized by Iterative Taguchi’s Method - Wei-Chung Weng; Chi-Keong Wong (IEEE Access)
This study proposes a novel 2.45 GHz wideband $2× 2$ circularly polarized (CP) slot antenna array, which consists of irregularly hexagonal slot CP antenna elements and a sequentially rotated phase feed network. The CP antenna element has a single-layer, single-fed, simple structure. Designing the CP antenna element does not require stacked layers, dual-feed networks, or additional resonant/perturbing components. The antenna element, including its hexagonal slot, is optimized using the iterative Taguchi’s optimization method to broaden the antenna’s impedance and axial ratio bandwidths. Detailed CP antenna design approaches, optimization settings, CP wave mechanisms, and the element’s and antenna array’s results, are discussed. Good agreements between measured and simulated results are revealed, confirming the validity of the proposed designs. The proposed wideband $2× 2$ CP irregularly shaped hexagonal slot antenna array provides a maximum boresight gain of 15.3 dBic and a CP bandwidth of 47.6% from 2.13 to 3.46 GHz. At the center frequency of 2.45 GHz, the cross-polarization level in the main beam direction is less than –23.6 dB; the front-to-back ratio is larger than 40 dB; and the back-lobe level is less than –22 dB. A comparison of the proposed array with other $2× 2$ wideband CP antenna arrays in the literature shows that it has a broader CP bandwidth and higher gain than those of all the compared antenna arrays. This study also demonstrates that irregular radiating geometries provide a novel approach to antenna design.